2019
DOI: 10.1002/ijc.32172
|View full text |Cite
|
Sign up to set email alerts
|

High response rates for T‐VEC in early metastatic melanoma (stage IIIB/C‐IVM1a)

Abstract: Talimogene laherparepvec (T‐VEC) is a modified herpes simplex virus, type 1 (HSV‐1), which can be administered intralesionally in patients with stage IIIB/C‐IVM1a unresectable melanoma (EMA label). The phase 3 OPTiM registration study showed an overall response rate (ORR) of 26%. Since December 2016, 48 eligible patients started treatment at the Netherlands Cancer Institute. We included 26 patients in this study with a follow up time ≥6 months, reporting Overall Response Rate (ORR), Disease Control Rate (DCR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 13 publications
4
45
0
Order By: Relevance
“…Franke et al from The Netherlands reported a single‐institution experience with T‐VEC monotherapy . In this study, 26 patients with stage IIIB–IVM1a melanoma treated with T‐VEC were included, with a follow‐up time ≥ 6 months.…”
Section: Real‐world Experiences With T‐vec In the Treatment Of Melanomamentioning
confidence: 99%
“…Franke et al from The Netherlands reported a single‐institution experience with T‐VEC monotherapy . In this study, 26 patients with stage IIIB–IVM1a melanoma treated with T‐VEC were included, with a follow‐up time ≥ 6 months.…”
Section: Real‐world Experiences With T‐vec In the Treatment Of Melanomamentioning
confidence: 99%
“…A current study based on a prospectively maintained database from the Netherlands Cancer Institute showed high complete and overall response rates in 26 stage IIIB/C in-transit melanoma patients. Twentythree patients were treatment-naïve [16]. The COSMUS-1 study investigated T-VEC treatment in the clinical practice setting in 78 patients in the USA, including 43.4% patients who received checkpoint inhibitors before T-VEC treatment or in combination and 30 patients with tumor stage IVM1b/c disease [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter chart review analyzed data from 27 patients treated with T-VEC in routine clinical practice in Germany [15]. In a current study by the Netherlands Cancer Institute, data from 26 T-VEC treated patients were analyzed based on a prospectively maintained database [16]. Recently, a real-world data study (COSMUS-1) comprising 76 patients in the USA has been published [17].…”
Section: Introductionmentioning
confidence: 99%
“…The herpes virus vaccine called T-VEC, engineered to selectively replicate in tumour cells and to secrete GM-CSF, has been approved by the FDA for intratumoural administration for stage IIIB/C-IV melanoma based on the phase 3 OPTiM trial [51,157], as mentioned above (see Section 2.2.1). A recently reported series of off-trial uses of T-VEC in early advanced melanoma (stages IIIB/C-IVM1a) showed a CR rate of 61.5% and a PR rate of 26.9, with a DCR of 92.3% [158].…”
Section: Oncolytic Virus Vaccinesmentioning
confidence: 96%